0207 Mothers' Adverse Childhood Experiences and Protective Factors are Associated with Rest-activity Rhythms in their Children. (25th May 2022) - Condon, Eileen; Jeon, Sangchoon; Sadler, Lois; Redeker, Nancy
Abstract: Introduction: Mothers' history of adverse childhood experiences (ACEs; e.g. maltreatment, household dysfunction) are associated with poor health outcomes in their children, but mechanisms underlying this intergenerational transmission are poorly understood. Given links between circadian rhythm and the stress-response system, we test the hypothesis that maternal ACEs influence child health through disrupted rest-activity rhythm (RAR) in the mother and child. We also explore whether mothers' benevolent childhood experiences (BCEs) are protective against disrupted RAR. Methods: We conducted a cross-sectional pilot study of maternal-child dyads with preschool-age children. Mothers reported history of childhood adversity (ACEs Scale, Childhood Trauma Questionnaire) and protective factors (BCE Scale). Dyads wore wrist actigraphs for 8-10 days and mothers completed daily electronic diaries. Nonparametric measures of RAR (e.g. interdaily stability [IS], intradaily variability [IV]) were calculated. We used linear regression to examine associations between mothers' childhood history and maternal and child RAR measures, controlling for household size and maternal employment. Results: Maternal-child dyads (N=20) identified as white (75%), Black (15%), and Hispanic/Latina (10%). Mean child age was 4.2 years (40% female). Average household size was 4.5 ±.1.1 and 65% of mothers were employed. Forty-two percent of mothers reported 1-2 ACEs and 25% reported 3 or more ACEs. Maternal childhood history was not associated with mothers' RAR. However, maternal ACEs and CTQ total score were associated with decreased child IS (ACEs: β= -0.47, SE=0.01, p=.02; CTQ total: β= -0.53, SE=.01, p=.001) and increased child IV (ACEs: β=0.29, SE=.01, p=.051; CTQ total: β=0.38, SE+.00, p=.03). CTQ subscales revealed maternal childhood physical abuse (β= -0.54, SE=.01, p<.0001), emotional abuse (β= -0.42, SE=.00, p=.002), and sexual abuse (β= -.73, SE=.00, p<.0001) were associated with decreased child IS, while maternal childhood emotional neglect was associated with increased child IV (β= 0.39, SE=.01, p=.04). Maternal BCEs were associated with decreased child IV (β= -0.44, SE=.01, p=.03). Conclusion: Maternal ACE history may influence child health through effects on children's circadian rhythm (i.e. decreased synchronization, increased fragmentation), while maternal BCEs may protect against rhythm fragmentation. Additional research is needed to support these novel preliminary findings. Support (If Any): National Institute of Nursing Research (K99NR018876) and American Nurses Foundation.